A suspect of large dentigerous cyst associated with impacted canine evaluated by CBCT: a case report in a young patient - Galih Rahmadini; Fahri Reza Ramadhan; Aga Satria Nurrachman; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This case report aims to describe a large radiolucent lesion associated with an impacted canine in a young patient from CBCT radiographs. Case Report: A 12-year-old boy was referred for CBCT examination to the Dentomaxillofacial Radiology unit at the Universitas Padjadjaran Dental Hospital with swelling on the right side of the face and a gingival lump on the upper right region suspected as an unerupted canine. The CBCT examination results showed an ectopic impacted tooth 13 and a large hypodense/radiolucent lesion with a well-defined and corticated border located on the coronal of tooth 13, expanding into the maxillary sinus and nasal cavity. Conclusion: Based on the CBCT result in terms of location and radiographic features, this extensive radiolucent lesion led to a suspect radiodiagnosis of the dentigerous cyst within a young patient. However, histology examination is still required to establish a definitive diagnosis.